Novel capillary and microfluidic devices for biological analyses - Klasner, Scott A. (Kansas State University, 2010)
As the field of separation science evolves so do the techniques, tools and capabilities of the discipline. The introduction of microfluidics stemmed from a desire to perform traditional analyses faster and on a much smaller scale. The small device sizes exploited in microfluidics permits the investigation of very small volumes of very dilute samples yielding information inaccessible by traditional macroscale techniques. All of the chapters presented in this dissertation illustrate attempts to supplement current microscale techniques with new tools, techniques and analysis schemes for looking at biologically relevant analyses. In chapter two I present the development and characterization of an amphiphilic polymer that has potential as a material for the fabrication of microfluidic devices. This material is composed of a poly(dimethylsiloxane)-poly(ethylene oxide) block copolymer and is dramatically more hydrophilic than the other polymeric materials currently used for the fabrication of microfluidic templates, mainly poly(dimethylsiloxane). Biomolecules such as proteins are notoriously hydrophobic and will tend to adsorb to other hydrophobic surfaces thus the use of a hydrophilic material may serve to reduce or eliminate this problem. The amphiphilic material is of a suitable durability for micromolding and molded channel architectures can be sealed between two layers of the material by simple conformal contact permitting the execution of high speed electrophoretic separations. Chapter three contains initial results obtained while investigating the fluorescent labeling and electrophoretic separation of ecdysteroids. Ecdysteroids are hormones found in insects that are responsible for controlling the process of molting. Here we attempted to analyze these molecules by employing a reactive fluorescent probe, BODIPY FL® hydrazide, that would target the α,β-unsaturated ketone group on the steroid, permitting its analysis by capillary electrophoresis with laser induced fluorescence detection. While optimistic initial results were obtained with the labeling and analysis of similar functional groups on model compounds such as progesterone, labeling of the ecdysteroid molecules was never achieved to a degree that would permit reliable analysis. In chapter four I report the development and use of a microimmunoaffinity column for the analysis of insect serine protease inhibitors, or serpins. These proteins play a very important role in the regulation of insect immune responses and their activity may play an integral role in the effective transmission of the malaria parasite by the mosquito Anopheles gambiae. A microimmunoaffinity column was constructed from magnets, poly(dimethylsiloxane), fused silica capillary and Protein A coated magnetic microspheres. In these initial studies, purified antibodies to serpin protein, as well as purified serpin protein, were used to prepare and investigate the ability to isolate, preconcentrate, and elute serpin proteins for subsequent analysis. By implementing this miniaturized system which incorporates very small fluid volumes we hoped to extend this technique to the analysis of very small samples, and eventually to the analysis of individual small insects. Our work indicates that it is possible to isolate, elute, and detect serpin protein on a traditional western blot membrane. Chapter five presents the development of a novel polymer blend for the fabrication of paper-based microfluidic devices and use of these devices in the performance of diagnostically relevant clinical assays. We took the concept of paper-based microfluidic devices and improved upon the current photoactive polymers used for their fabrication by developing a polymer blend using an acryloxy modified siloxane polymer as well as a commercially available photoactive adhesive, Norland Optical Adhesive 74. This blended polymer resulted in a dramatic reduction in fabrication time as well as improved resolution permitting the reliable patterning of small feature sizes. We also report for the first time a demonstration of these devices performing a two-step spatially separated online chemical derivatization facilitating the analysis of urinary ketones. These devices are predominantly used for the analysis of urine, and their application was extended to the quantitation of nitrite in saliva for the purposes of hemodialysis monitoring. While varied in application, all of the data presented in this dissertation exploits the power of miniaturization to improve current methods of analysis and to extend macroscale techniques to trace biological analytes.
Keywords: Microfluidics; Immunoaffinity chromatography; Paper-based devices; Ecdysteroids; Poly(dimethylsiloxane); Photolithography; Chemistry, Analytical (0486)